Cultivar‐dependent increases in mycorrhizal nutrient acquisition by barley in response to elevated CO2. Issue 5 (4th December 2020) - Thirkell, Tom J.; Campbell, Matthew; Driver, Josephine; Pastok, Daria; Merry, Beverley; Field, Katie J.
Societal Impact Statement: Modern agriculture is under pressure to meet yield targets while reducing reliance on finite resources to improve sustainability. Climate change represents an additional challenge—elevated atmospheric CO2 concentrations may increase plant growth and boost yield, but the nutritional value of crops grown at elevated CO2 is often reduced. Arbuscular mycorrhizal fungi (AMF) can improve plant nutrition, although how this symbiosis will be affected by climate change is unclear. Here, we demonstrate mycorrhizal contribution to nitrogen and phosphorus nutrition in barley under current and future CO2 concentrations. In one cultivar, AMF substantially increased phosphorus uptake at elevated CO2 and prevented phosphorus dilution, suggesting the symbiosis may become more important for crop nutrient uptake in the future. Summary Globally important cereals such as barley ( Hordeum vulgare L.) often engage in symbiosis with arbuscular mycorrhizal fungi (AMF). The impact of elevated atmospheric CO2 on nutrient exchange between these symbionts remains unknown. In controlled environment experiments, we used isotope tracers ( 15 N, 33 P, 14 C) to quantify nutrient fluxes between two barley cultivars (Moonshine and Riviera) and their associated AMF at ambient (440 ppm) and elevated (800 ppm) CO2 . Elevated CO2 reduced shoot N concentration in Moonshine, and shoot N and P concentration in Riviera. Elevated CO2 substantially increased mycorrhizal 33 P acquisition in Moonshine. Mycorrhizal contribution to P uptake in Moonshine may have prevented dilution of tissue P concentration at elevated CO2 . In Riviera, AMF did not improve 33 P acquisition. Both cultivars received 15 N from their AMF symbionts, and this acquisition was not influenced by CO2 concentration, although Moonshine received more 15 N than Riviera. Our results suggest that AMF may provide substantial contributions to barley nutrition at current and projected future CO2 concentrations. This is especially noteworthy for barley, which is generally considered to have low mycorrhizal receptivity. AMF may help alleviate or avoid nutrient dilution normally observed at elevated CO2 . Variation between cultivars indicates that mycorrhizal contribution to cereal nutrition could be improved through selective breeding practices. Abstract : Modern agriculture is under pressure to meet yield targets while reducing reliance on finite resources to improve sustainability. Climate change represents an additional challenge—elevated atmospheric CO2 concentrations may increase plant growth and boost yield, but the nutritional value of crops grown at elevated CO2 is often reduced. Arbuscular mycorrhizal fungi (AMF) can improve plant nutrition, although how this symbiosis will be affected by climate change is unclear. Here, we demonstrate mycorrhizal contribution to nitrogen and phosphorus nutrition in barley under current and future CO2 concentrations. In one cultivar, AMF substantially increased phosphorus uptake at elevated CO2 and prevented phosphorus dilution, suggesting the symbiosis may become more important for crop nutrient uptake in the future.